Construction and evaluation of SAK-HV protein oral dosage form based on chitosan quaternary ammonium salt-PLGA microsphere. (26th November 2019) - He, Shiming; Fu, Wenliang; Zou, Minji; Xing, Weiwei; Liu, Zhongcheng; Xu, Donggang
Abstract: The aim of this study was to realize the oral delivery of SAK-HV protein and improve its oral bioavailability based on chitosan quaternary ammonium salt-PLGA microsphere. The results showed that the SAK-HV-loaded microsphere can overcome the multiple obstacles for oral adsorption and adhere effectively to the jejunal segment of a rat. The pharmacokinetic analysis of the oral drug-loaded microspheres in rats showed that the blood drug concentration of SAK-HV reached the peak value at 4 h after oral administration, and the relative oral bioavailability of SAK-HV was 3.4%. Additionally, after oral administration to the mice, a higher level of antibody against SAK-HV was produced on day 21 compared with that in the control and injection groups, and the antibody titre was 7.2 times that of the tail vein group. This work suggests that the microsphere of the chitosan quaternary ammonium salt-PLGA may be a promising drug delivery system for the oral administration of SAK-HV protein.